Analisis Analisis Pendapatan Usaha Warung Tradisional dengan Munculnya Minimarket di Kota Denpasar - Ratika Dewi, Ida Ayu Sima; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 12, Desember 2017 (pp. 2352 - 2582), 2017)
This study aimed to determine the effect of simultaneous and partial turnover penjulan, distance effort, and hours of operation to changing revenue haberdasher in Denpasar after emergence minimarket. The data used in this study are primary data, by distributing questionnaires to grocer in Denpasar. The samples used are as many as 94 haberdasher. The analysis technique used in this study is binary logistic regression analysis. The result showed that sales turnover, within the business, and hours of operation jointly have significant effect on earnings haberdasher in Denpasar. Variable sales turnover partially have positive and significant impact on the income haberdasher in Denpasar. Variable distance effort partially have positive and significant impact on the income haberdasher in Denpasar. Variable operating hours partially have positive and significant impact on the income haberdasher in Denpasar.